End Stage Therapy and Heart Transplantation (IntechOpen, 2024)
Over the last two decades, there has been steady progress in therapeutic strategies for end-stage heart failure, such as advanced heart failure medical therapy and mechanical circulatory support before and after heart transplantation, as well as heart transplantation. This book provides a comprehensive overview of these advancements. It includes eight chapters that address topics such as cardiac reshaping nets, extracorporeal membrane oxygenation (ECMO), left ventricular assist devices (LVADs), heart transplantation in the Middle East and Japan, and more.